(untitled) (Annals of Medical Research, 2023)
Aim: The increase of oxidatif stress caused by hyperglycemia in diabetes contributes to diabetic complications such as nephropathy. Experimental Diabetes Mellitus (DM) was induced with streptozotocin. Thioctic acid (TA), which has antioxidant properties, is a vital cofactor of mitochondrial respiration enzymes. This study investigated whether TA administration could reduce oxidative stress to treat diabetic nephropathy. Materials and Methods: 40 male Wistar albino rats were divided to groups: Control, DM, TA and DM+TA. TA and DM+TA group was administered 100 mg/kg/day TA daily, and blood glucose was assessed for six weeks. The superoxide dismutase, glutathione peroxidase and catalase activities, glutathione levels, malondialdehyde (MDA), protein carbonyl (PC), total antioxidant (TAS), total oxidant status (TOS) and OSI also were evaluated. Results: MDA and PC were increased, and antioxidant capacity was decreased in the diabetic groups compared to Control (p <0,05). In the DM+TA group, MDA, PC and TOS were decreased and TAS was increased compared to the DM group (p <0,05). Conclusion: TA exhibited a curative effect on diabetic nephropathy by increasing antioxidant activity and reducing oxidative damage.